2013
DOI: 10.1186/1479-5876-11-170
|View full text |Cite
|
Sign up to set email alerts
|

Importance of leptin signaling and signal transducer and activator of transcription-3 activation in mediating the cardiac hypertrophy associated with obesity

Abstract: BackgroundThe adipokine leptin and its receptor are expressed in the heart, and leptin has been shown to promote cardiomyocyte hypertrophy in vitro. Obesity is associated with hyperleptinemia and hypothalamic leptin resistance as well as an increased risk to develop cardiac hypertrophy and heart failure. However, the role of cardiac leptin signaling in mediating the cardiomyopathy associated with increased body weight is unclear, in particular, whether it develops subsequently to cardiac leptin resistance or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…Our results have suggested a role of the STAT3/c‐Myc pathway in miR‐16 down‐regulation during hypertrophy, as pharmacological inhibition of either STAT3 or c‐Myc prevented the down‐regulation of miR‐16 and subsequent hypertrophy. This conclusion has been supported by previous studies showing that STAT3 activation is involved in the development of cardiac hypertrophy . In addition, a previous study reported that the STAT3/c‐Myc pathway mediated miR‐16 suppression by progestin in mammary tumour cells , further supporting our conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…Our results have suggested a role of the STAT3/c‐Myc pathway in miR‐16 down‐regulation during hypertrophy, as pharmacological inhibition of either STAT3 or c‐Myc prevented the down‐regulation of miR‐16 and subsequent hypertrophy. This conclusion has been supported by previous studies showing that STAT3 activation is involved in the development of cardiac hypertrophy . In addition, a previous study reported that the STAT3/c‐Myc pathway mediated miR‐16 suppression by progestin in mammary tumour cells , further supporting our conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the JAK2 kinase may induce phosphorylation of Tyr705 on the STAT3 that bound with the receptor, and then the activated STAT3 would enter the nucleus in a form of a dimer to bind specifically with the DNA sequences to trigger the expression of downstream target genes such as cyclin D1 , c-myc , c-Jun , bcl , bcl-xL , and mcl-I . These genes were reported to modulate the cell cycle and inhibit the cell apoptosis, which may be participated in the protective effects of vascular endothelial barrier function [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports that the insulin resistance induced by obesity with associated hyperinsulinaemia could promote cardiac remodelling via the growth-promoting properties of insulin or by attenuating the anti-apoptotic signalling of the phosphatidylinositol 3'-kinase (PI3K)- Akt (protein kinase B [PKB]) pathway elicited by insulin receptor activation [ 59 , 61 ]. In addition to insulin, the literature also highlights that leptin induces cardiomyocyte hypertrophy in rodents [ 62 ]. Thus, hyperleptinemia presented by Ob animals may promote the activation of Ras homolog gene family, member A (RhoA)/Rho-associated coiled-coil-forming protein kinase (ROCK) and p38 mitogen-activated protein kinase (MAPK) protein translocation to the nucleus by its receptor, resulting in cardiomyocyte hypertrophy [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%